SISTEM INFORMASI AKUNTANSI PENJUALAN PADA CV. YKZ - setiawan; Yopy Ratna Dewanti; Muhamad Sholeh; Jaenudin Akhmad (ASIAN PUBLISHER, 2024)
Technology Development plays the role in influencing modernization of tax system one of them is e-Filing System. E-Filing is a tax filing system electronically that facilitates taxpayers in submitting Tax Return anytime and anywhere. The objective of this study is to analyze the implementation of policy on individual tax e-Filing, obstacles encountered and efforts undertaken in coping with such obstacles at the Public Work and Spatial Planning Office of Depok. This study used qualitative descriptive research method. Result of this study identified that the implementation of e-Filing has been good enough. Some obstacles which can be overcome with efforts carried out from the implementor and taxpayer.